Lift Off: Exploring the Universe - Shackleton, Caroline; Nathan Paul Turner
From science fiction to actual space exploration, we have always been fascinated by our universe. Landing on the moon and exploring Mars aren't science fiction anymore. What will humans do in space next?
Keywords: English language Textbooks for foreign speakers; Readers (Elementary); Readers (Adult); Textbooks for foreign speakers; Exploration of outer space